(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
he 1785-1786 crisis is considered as a food crisis. he loss of harvest caused a high death toll in New Spain, due to famine and the weakness of the population exposed to various illnesses. Among the main initiatives in Michoacán were those of Bishop Obispo Fray Antonio de San Miguel and Dean José Pérez Calama, aiming at avoiding serious social problems which entailed the lack of food and its high price. he measures taken by the town council and the counsil of canons were successful in avoiding the scarcity and shortage in corn, however, a lot of people died in this period, especially in 1786. he high death toll can be explained by the epidemics which started to spread in Virreinato. here are testimonies and research papers on the high number of human lives taken by the plague, whereby the general reason for death was high fever. hese crises had diferent impacts on the various towns that this study focuses on: Valladolid, Pátzcuaro y Uruapan, partly due to the quality of parish registers, but also because the various illnesses were treated diferently among diferent age groups. heir impact can be measured by Lorenzo del Panta and Massimo Livi-Bacci’s formula, applied in death registers. he crises brought by the arrival of migrants from El Bajío, who probably brought with them the epidemics that spread in Michoacán.